Manifestaciones de violencia contra las mujeres, Argentina (1880-1910) - Lobato, Mirta Zaida (Anuario de Historia de América Latina, 2023)
This article analyzes various forms of violence against women, particularly those of the working classes, in a society that was undergoing fast transformation between the end of the 19th century and the first decade of the 20th century. In that context, gender relations were rearranged in different ways in the face of changes in society. Episodes of violence against women by men reached the courts and the press. Through the examination of court files from the city and province of Buenos Aires, I pay attention to police and judicial procedures that often ended in the release of the accused. I also analyze mass-circulation publications that took these episodes and made them focus of interest for a wide public. Through particular stories, I inquire how these types of publications created empathy with the victims.
Keywords: Violence Against Women; Gender; Justice; Argentina